2009
DOI: 10.1158/0008-5472.can-09-2604
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Paradigm to Trigger Apoptosis in Chronic Lymphocytic Leukemia

Abstract: Evasion of apoptosis is a hallmark of chronic lymphocytic leukemia (CLL), calling for new strategies to bypass resistance. Here, we provide first evidence that small-molecule X-linked inhibitor of apoptosis (XIAP) inhibitors in combination with the death receptor ligand tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) present a novel approach to trigger apoptosis in CLL, including subgroups with resistant disease or unfavorable prognosis. XIAP, cellular IAP (cIAP) 1, and cIAP2 are expressed at h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
30
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 50 publications
4
30
0
Order By: Relevance
“…Thus, by demonstrating that IAP inhibitors and lexatumumab synergistically trigger apoptosis in a RIP1-dependent and TNF␣-independent manner in RMS cells, our findings have important implications for the development of experimental treatment strategies for RMS. Beyond RMS, this study, together with our previous reports (18,(35)(36)(37)(38), underscores the broader relevance of the concept of simultaneously targeting IAP proteins and TRAIL receptors as a promising anticancer strategy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, by demonstrating that IAP inhibitors and lexatumumab synergistically trigger apoptosis in a RIP1-dependent and TNF␣-independent manner in RMS cells, our findings have important implications for the development of experimental treatment strategies for RMS. Beyond RMS, this study, together with our previous reports (18,(35)(36)(37)(38), underscores the broader relevance of the concept of simultaneously targeting IAP proteins and TRAIL receptors as a promising anticancer strategy.…”
Section: Discussionsupporting
confidence: 65%
“…The concept of simultaneously targeting IAP proteins and TRAIL receptors is, in principle, suitable for clinical translation because IAP antagonists and anti-TRAIL receptor antibodies have individually already entered the stage of early clinical evaluation (33,34). In addition, we previously reported that IAP inhibitors preferentially prime various cancer types, but not non-malignant cells, to TRAIL receptor-induced apoptosis, pointing to some cancer selectivity (35)(36)(37). Thus, by demonstrating that IAP inhibitors and lexatumumab synergistically trigger apoptosis in a RIP1-dependent and TNF␣-independent manner in RMS cells, our findings have important implications for the development of experimental treatment strategies for RMS.…”
Section: Discussionsupporting
confidence: 55%
“…While some other studies using different Smac mimetics reported no correlation between cell death induction by Smac mimetic and biological parameters in primary CLL, 39,40 two studies using IAP inhibitors plus tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) showed cell death induction in CLL cases with poor prognosis. 13,41 Using whole-genome gene expression profiling, we identify two functional categories that are most significantly modulated by BV6, i.e., programmed cell death and NF-jB pathway, across tumor entities not only in CLL but also in primary CBF AML samples, underlining the broader relevance of this finding. Concomitant experiments demonstrate that treatment with BV6 activates NF-jB signaling and cell death pathways in primary CLL cells.…”
Section: Discussionmentioning
confidence: 94%
“…IAP proteins, in particular XIAP, are overexpressed in CLL and this overexpression confers chemoresistance and is associated with a progressive course. [11][12][13][14] To counter IAP proteins several small-molecule IAP inhibitors, including Smac mimetics, have been developed. 15 It has been shown that Smac mimetics abrogate XIAP-mediated caspase inhibition and induce autoubiquitination and rapid proteasomal degradation of cIAP1 and-2, leading to activation of NF-jB and TNFa production that triggers cell death in an autocrine/paracrine fashion.…”
mentioning
confidence: 99%
See 1 more Smart Citation